Initial effects of the expansion and enforcement of a subtropical marine reserve on threatened shark species - Motta, Fabio S.; Rolim, Fernanda A.; Athayde, Ana Clara S.; Gragnolati, Maisha; Munhoz, Rafael R.; Chelotti, Luiza D.; Andres, Nauther; Pereira-Filho, Guilherme H.; Gadig, Otto B. F. [UNESP] (Springer Nature, 2024)
Balanced ecosystems benefit meso and top predators, which help to maintain the quality of the habitat. Thus, the presence of sharks can be considered an indicator of environmental health. Baited remote underwater stereo-videos (BRUVs) were used to assess the relative abundance of sharks in the Alcatrazes Archipelago, Southwestern Atlantic, after an important no-take zone expansion from 12 to 675 km2 with the creation of the Wildlife Refuge and enhanced enforcement, comparing our findings with previous BRUV surveys. This study observed sharks in 16 (10.7%) of the 150 stereo-BRUV deployments and recorded seven species (Squalus cf. albicaudus, Carcharias taurus, Carcharhinus plumbeus, Carcharhinus falciformis, Rhizoprionodon porosus, Sphyrna lewini, and Sphyrna zygaena). These data, combined with the perception of frequent and experienced divers (management staff and diving operators) about the increase in shark sightings, suggest a recent positive effect of the no-take zone for these predators and a healthier ecosystem. Results also show that long-term monitoring and effective enforcement of the Alcatrazes Wildlife Refuge are crucial to maintain and enhance the positive effects in the area.
Keywords: BRUV; Conservation; Elasmobranchs; Marine protected areas; Southwestern Atlantic; Threatened species